2010
DOI: 10.3109/15360288.2010.523066
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Intrathecal Opioid Pump and Spinal Cord Stimulation for Pain Management: Analysis of 11 Patients With Failed Back Surgery Syndrome

Abstract: Dual-modality management of failed back surgery syndrome (FBSS) using a combination of an intrathecal opioid pump (IOP) and spinal cord stimulator (SCS) has not been investigated. The authors performed a retrospective review of 11 patients (8 men, 3 women) with FBSS who underwent nonsimultaneous surgical implantation of both an IOP and a thoracic SCS. Chart review and structured phone interviews were performed to obtain follow-up. Of the two modalities, 3 patients (27%) had an IOP placed first and 8 patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 41 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…With this background, many clinical trials intended to relieve pain in patients with FBSS have been conducted. Various medications (11)(12)(13)(14), re-operation (15)(16)(17)(18), exercise therapy (19,20), spinal cord stimulation (SCS) (21)(22)(23)(24)(25)(26)(27)(28)(29)(30), epidural adhesiolysis (9,(31)(32)(33)(34), epidural injection (35)(36)(37), intrathecal infusion (38)(39)(40)(41) or psychotherapy (42) have been suggested as treatment options for FBSS. However, their clinical effects have not been clearly determined.…”
Section: Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…With this background, many clinical trials intended to relieve pain in patients with FBSS have been conducted. Various medications (11)(12)(13)(14), re-operation (15)(16)(17)(18), exercise therapy (19,20), spinal cord stimulation (SCS) (21)(22)(23)(24)(25)(26)(27)(28)(29)(30), epidural adhesiolysis (9,(31)(32)(33)(34), epidural injection (35)(36)(37), intrathecal infusion (38)(39)(40)(41) or psychotherapy (42) have been suggested as treatment options for FBSS. However, their clinical effects have not been clearly determined.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Although both studies showed decreased back pain with additional subcutaneous stimulation, they were not reliable due to the small sample size (89,90). Intrathecal infusion of opioids was also investigated and the effectiveness and safety were suggested in 2 case series (40,41). Interestingly, the usefulness of a capsaicin 8% patch was proposed (91).…”
Section: Other Treatment Modalitiesmentioning
confidence: 99%
“…When a more specific diagnosis is lacking, patients with FBSS rely on pharmacological, physical, and cognitive‐behavioral therapy, but studies of these therapies specifically for FBSS are lacking . Spinal cord stimulation , intrathecal opioids , adhesiolysis , and caudal epidural injections have been used. Revision surgery is sometimes undertaken .…”
Section: Introductionmentioning
confidence: 99%
“…Tomycz et al performed a retrospective analysis of 11 patients who were simultaneously implanted with IDDS and spinal cord stimulators (SCS). 113 While all 11 patients (100%) stated that the dual system improved their quality of life, six patients (55%) felt that their relief from the IDDS was superior to SCS. 113 Hayek et al performed a retrospective analysis of 57 patients with IDDS administration of hydromorphone and bupivacaine for postlaminectomy syndrome.…”
Section: Intrathecal Drug Delivery Systemsmentioning
confidence: 96%
“… 113 While all 11 patients (100%) stated that the dual system improved their quality of life, six patients (55%) felt that their relief from the IDDS was superior to SCS. 113 Hayek et al performed a retrospective analysis of 57 patients with IDDS administration of hydromorphone and bupivacaine for postlaminectomy syndrome. 114 At 24 months, pain scores had decreased from 8.42 to 4.3 ( P <0.001).…”
Section: Intrathecal Drug Delivery Systemsmentioning
confidence: 96%